Therapeutic potential of histamine H4 receptor agonists in triple-negative human breast cancer experimental model - Martinel Lamas, Diego José (2013)
The presence of the histamine H₄ receptor (H₄R) was previously reported in benign and malignant lesions and cell lines derived from the human mammary gland. The aim of this work was to evaluate the effects of H₄R ligands on the survival, tumour growth rate and metastatic capacity of breast cancer in an experimental model.